Cause-and-effect Analysis of Anthropogenic and Natural Aspects in the Process of Assessing the Material Heritage Resource in Underground Mining Adaptation Planning - Radziejowska, Aleksandra; Wieja, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The ongoing energy transformation requires legal and economic intervention by the Polish government to phase out unprofitable mining enterprises, especially in the coal mining sector. The poorly executed process mentioned above may lead not only to environmental degradation but also to social problems (rupture of interpersonal relationships, elimination of traditions, eradication of cultural behaviors). Therefore, an effective solution to this problem may be the adaptation of the aforementioned facilities for tourism purposes.
Keywords: analysis; adaptation; underground mining heritage; heritage preservation; DEMATEL